The Effects of Major Depressive Disorder on the Sequential Organization of Information Processing Stages: An Event-Related Potential Study - Daniel Kwasi Ahorsu; Ken Chung; Ho Hon Wong; Michael Gar Chung Yiu; Yat Fung Mok; Ka Shun Lei; Hector Wing Hong Tsang (Brain Sciences, 2020)
The adverse effects of depression on patients’ life have been reported but information about its effects on the sequential organization of the information processing stages remains poorly understood as previous studies focused only on distinct stages. This study adds to existing knowledge by examining the effect of major depressive disorder (MDD) on the sequential organization of information processing, executive and community functioning. Fifty-seven participants with 19 participants each for first episode depression (FMDD), recurrent episodes depression (RMDD), and healthy controls (HCs) participated in this study. They completed assessments on executive and community functioning measures, and choice reaction time task (CRTT) for the event-related potential (ERP) data. Findings revealed no significant between-group difference in executive functioning but participants with depression (FMDD and RMDD) were found to be more depressed, with FMDD participants having worse community functioning skills compared with HCs. There was no significant between-group main effect on behavioral data. ERP data showed significantly less positive-going P3b among RMDD participants compared with HCs. FMDD participants used a different information processing strategy at P1, while HCs and RMDD participants used a different processing strategy at N2b compared with the other group(s), respectively. The results suggest the use of multifaceted assessment to get a holistic view of the health status of people with MDD in order to inform clinicians on the appropriate interventional strategies needed for the patient.